Digital innovation management for entrepreneurial ecosystems: services and functionalities as drivers of innovation management software adoption - Herbert Endres; Stefan Huesig; Robin Pesch (Review of Managerial Science, 2021)
Innovation Management Software can promote Entrepreneurial Ecosystems by consolidating an organization's innovation programs, stakeholders, and resources in one place. In this study, we highlighted the digitalization of innovation processes. We focus particularly on the factors influencing the adoption of a specific class of software tools called Innovation Management Software (IMS) or Digital Innovation Management System to support innovation management methods and activities. Specifically, we address the two questions (a) which specific functionality drives the adoption of IMS tools, and (b) which services of IMS providers are valuable in supporting the adoption of IMS by organizations aiming to digitalize their innovation processes. By using an online questionnaire, we gathered survey data from 199 innovation managers of German firms. We used regression analysis to test our hypotheses. While the overall IMS adoption is considered to positively affect the new product development (NPD) efficiency, our results indicate that especially idea management functionalities and services for updates and upgrades improve the IMS adoption. Surprisingly, offering complementary consulting services together with IMS offerings to support the digitalization of innovation processes reduces the likelihood of IMS adoption. These findings are important for managers, consultants, and developers in order to choose and leverage the right options for improving the adoption of IT tools in the NPD process and therefore increase NPD performance and thus also promote Entrepreneurial Ecosystems.
Keywords: O31; 650; Adoption; Digitization; Digital transformation; Digital innovation management system; Entrepreneurial ecosystem; Innovation management; Digital services; New product development performance